Fingerprint composition and aging: A literature review. Issue 4 (July 2015) - Cadd, Samuel; Islam, Meez; Manson, Peter; Bleay, Stephen
Abstract: Fingerprints have a key role in criminal investigations and are the most commonly used form of evidence worldwide. Significant gaps remain however, in the understanding of fingerprint chemistry, including enhancement reaction mechanisms and the effect of environmental variables and time on composition. Determining the age of a fingerprint is also a relatively unexplored area. A successful method, with reliable and quantitative estimates, would have numerous advantages. Previous unreliable methods have predominantly focused on enhancement success based on physical and chemical changes. This review explores variations in composition due to donor characteristics and environmental variables, and identifies gaps for further research. We also present a qualitative and quantitative summary of the effect of time on composition. Kinetics are presented where known, with summary schematics for reaction mechanisms. Previous studies exploring methods for determining the age of a fingerprint are also discussed, including their advantages and disadvantages. Lastly we propose a potentially more accurate and reliable methodology for determining fingerprint age based on quantitative kinetic changes to the composition of a fingerprint over time. Highlights: Significant gaps exist in current knowledge of fingerprint chemistry. Differences in fingerprint composition can be used for donor individualisation. A method for determining fingerprint age would be a significant breakthrough. Previously proposed methods are unreliable and inaccurate. We propose a method to determine age based on changes to composition over time.